FRAND-Encumbered SEPs and Injunctions: Why Section 5 of the FTC Act is an Inappropriate Remedy - Miller, Benjamin M. (Science and Technology Law Review, 2015)
When a standard setting organization (SSO) for an industry establishes an industry standard, and that standard utilizes a standard essential patent (SEP), every participant in that industry who desires to practice the standard is required to use that particular patent. In today’s high-speed, interoperable, and global economy, SEPs provide valuable benefits to consumers by fostering uniformity and compatibility. However, an agreement by an entire industry to use a single patent confers a special power on the holder of that patent to control access to a given product market, due to the traditional right of a patent holder to exclude others from using its patent. To prevent hold-up, an SSO typically requires the holder of an SEP to agree to license the patent either on a royalty-free basis or at a fair, reasonable, and non-discriminatory (FRAND) rate. In reality, however, SEP holders do not always abide by their FRAND commitments and sometimes seek injunctions against industry participants wishing to utilize the standard. The dilemma facing private parties, courts, and government agencies is how to address these breaches of FRAND commitments. This Note focuses on one response—the Federal Trade Commission’s use of Section 5 of the Federal Trade Commission Act. After analyzing prior Section 5 enforcement actions in this area, this Note recommends that the FTC should refrain from enforcing Section 5 against the holders of FRAND-encumbered SEPs that seek injunctions on the use of their patents. First, the FTC has failed to provide sufficient guidance to industry participants on what conduct it considers harmful to competition. Further, the lack of guidance provided by the FTC’s prior enforcement actions does not show any commitment to applying consistent principles to future cases. The current procedure for FTC enforcement actions is not capable of establishing sufficient clarity. Second, the FTC has not demonstrated what, if any, competitive harm results from the holder of a FRAND-encumbered SEP obtaining an injunction; in fact, disallowing injunctions may create its own competitive harm. Only when the FTC finds competitive harm from obtaining an injunction should it bring a Section 5 case. Third, the FTC has not adequately considered the substantial benefits that result from the general use of SEPs and from allowing injunctions, and how its enforcement action may ultimately undermine those benefits. Lastly, the ability of and incentive for SEP holders and other interested parties to pursue other methods of resolution counsels against the use of Section 5. In light of these effects, the use of Section 5 will tend to chill innovation and harm consumer welfare—an outcome contrary to the goals of antitrust law. Until the FTC can provide adequate guidance to address these concerns, provide clarity to market participants, and show that anticompetitive harm results when the holder of a FRAND-encumbered SEP seeks an injunction, the agency should refrain from bringing Section 5 actions in this context. Only through issuing clear enforcement guidelines can the FTC ensure that it encourages innovation and benefits consumers, both domestically and abroad.